International Financial Statistics, October 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
This October 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. This issue presents countries newly reporting monetary data for Rwanda using the standardized report forms. Exchange rates in IFS are classified into three broad categories, reflecting the role of the authorities in determining the rates and/or the multiplicity of the exchange rates in a country. Although the method of calculating the US dollar/SDR exchange rate has remained the same, the currencies' number and weight have changed over time. Their amount in the SDR basket is reviewed every five years. When a country joins the IMF, it is assigned a quota that fits into the structure of existing quotas. Quotas are considered in the light of the member's economic characteristics and considering quotas of similar countries.